Brief measurement of X-ray spectra using a lutetium-yttrium-oxyorthosilicate crystal and a micro-photomultiplier tube. (December 2017) - Sato, Eiichi; Oda, Yasuyuki; Ishii, Tomotaka; Hagiwara, Osahiko; Matsukiyo, Hiroshi; Enomoto, Toshiyuki; Watanabe, Manabu; Kusachi, Shinya
Abstract: Brief measurement of X-ray spectra using a detector, consisting of an LYSO [Cerium doped Lutetium Yttrium Oxyorthosilicate, (Lu, Y)2 SiO5 :Ce] crystal and a μPMT (micro-photomultiplier tube) is described. X-ray photons are detected using the LYSO crystal and a 0.5-mm-diameter 3.0-mm-thick lead pinhole, and scintillation photons produced in the crystal are detected using the μPMT. The negative output voltages from the μPMT are input to a high-speed inverse-voltage-voltage amplifier, and the event pulses from the amplifier are sent to a multichannel analyzer to perform pulse-height analysis. Dark counts from the μPMT are not counted at all by increasing the time constant of the amplifier. Without the pinhole, the energy resolutions was approximately 40% at 59.5 keV. The photon energy was determined using two-point calibration using iodine-Kα fluorescence and tungsten Kα-photons from an X-ray-tube target. At a tube voltage of 100 kV, the maximum tube current without event-pulse pileups was 0.24 mA. Using the LYSO-μPMT detector, both the maximum and maximum-count energies increased with increasing tube voltage, and the maximum count rate was 72 kilocounts per second at a tube voltage of 100 kV and a current of 0.24 mA. Dual-energy computed tomography utilizing K- and L-edges was accomplished using gadolinium contrast media. Highlights: X-ray spectra were measured using LYSO-μPMT detector and pinhole. High-speed inverse amplifier for μPMT has been developed. Zero dark counting was carried out to detect low-energy photons. Energy calibration was performed using Kα photons of iodine and tungsten. L- and K-edge CT was accomplished simultaneously using Gd media.